PENERAPAN LIMA NILAI BUDAYA KERJA DALAM PENGELOLAAN DAN PENINGKATAN OMZET KOPERASI PEGAWAI NEGERI (KPN) KOPENDA KEMENTERIAN AGAMA KOTA PONTIANAK - Rosadi Rosadi; Ahmadi Ahmadi (CV. ADIBA AISHA AMIRA, 2024)
The Civil Service Cooperative (KPN) Kopenda of the Ministry of Religion (Kemenag) of Pontianak City experiences an increase in assets every year. Not only that, the remaining operating results (SHU) also experienced an increase. The increase in assets and SHU every year has made KPN Kopenda one of the healthy cooperatives in Pontianak City. Behind this increase is closely related to the five work cultural values that are carried out by the management and supervisors of KPN Kopenda. The five values of work culture are values that must be carried out by every employee within the Ministry of Religion (Kemenag) of the Republic of Indonesia. This study aims to understand how the five values of work culture affect the operational productivity and management KPN Kopenda Kemenag in increasing omzet and SHU. This is important so that cooperatives within Kemenag can implement the five values of work culture in increasing turnover and SHU. The results obtained were that the application of the five work cultural values was able to increase turnover and SHU in Kopenda Kemenag Pontianak